Single Parents' Communication Style in Guiding Children's Behavior According to Islamic Law in Simalungun Regency - Iqbal Saputra; Faridah (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to describe the communication style of single parents in guiding children's behavior according to Islamic law, and to describe how to guide parents and its impact on children. This study was conducted in Dolok Malela Village, Simalungun Regency using qualitative research methods. Data collection techniques in this study were through observation, interviews and documentation. The subjects in this study were 7 single parents. Data analysis conducted in this study consisted of three (3) stages including data reduction, data presentation, and drawing conclusions. The results of this study indicate that communication style is closely related to the parenting style of single parents in educating different children, namely the authoritarian communication style of 3 people and its influence on children, namely being able to instill Islamic values ​​but not having a social attitude, 3 single parents using an authoritative communication style and having an impact on children, namely being able to form children to deepen Islamic educational values ​​and having a high social attitude, and 1 single parent applying a permissive communication style and its impact on children is not fully able to guide children to behave according to Islamic law. but having a high social attitude.